Management of postoperative enterocutaneous fistulae in children: A decade experience in a single centre - Francis A Uba; Stella C Uba; Emmanuel O Ojo (Wolters Kluwer Medknow Publications, 2012)
Background: Enterocutaneous fistula (ECF) in children poses a lot of management challenges due to sepsis, malnutrition, fluid and electrolyte deficits, which are frequent complications. Knowledge of prognostic factors of postoperative ECF is essential for therapeutic decision-making processes. This study examined the variables that relate to the outcomes of management of ECF in children. Patients and Methods: Consecutive children who were managed for postoperative ECF in our unit between 2000 and 2009 were evaluated. Data were analysed for clinical features, management and its outcome. Results: A total of 54 patients were managed for ECF. Majority of the fistulas were due to operation for infective causes, with typhoid intestinal perforation ranking the highest. Overall, spontaneous closure without operative intervention occurred in 29 (53.7%) patients. Twenty-one (38.9%) patients required restorative operations to close their fistulas, which was successful only in 12 (22.2%) patients. There was a strong correlation between high-output fistulas (jejunal location) and surgical closure (P<0.001). Hypoalbuminaemia and jejunal location profoundly resulted in non-spontaneous closure of ECF (P<0.001) and were associated with high morbidity (P<0.001). Thirteen (24.1%) patients died due to hypokalaemia, sepsis and hypoproteinaemia/hypoalbuminaemia. Conclusions: Majority of the ECF in children closed spontaneously following high-protein and high-carbohydrate nutrition. Hypoalbuminaemia and jejunal location were important prognostic variables resulting in non-spontaneous closure, while hypokalaemia, sepsis and hypoproteinaemia/hypoalbuminaemia were associated with high mortality in children with ECF.